2007
DOI: 10.1165/rcmb.2007-0072oc
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Pathway Involved in Neutrophil Elastase–Stimulated MUC1 Transcription

Abstract: We previously reported that neutrophil elastase (NE) stimulated MUC1 gene expression in A549 lung epithelial cells through binding of Sp1 to the MUC1 promoter element. The current study was undertaken to elucidate the complete signaling pathway leading to Sp1 activation. Using a combination of pharmacologic inhibitors, dominantnegative mutant, RNA interference, and soluble receptor blocking techniques, we identified a protein kinase Cd (PKCd) / dual oxidase 1 (Duox1) / reactive oxygen species (ROS) / TNF-a-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…TNF-a stimulates the expression of MUC1 in A549 cells (39,40), human uterine epithelial cells (41), and human prostate cells (42). The molecular mechanism of the TNF-a-induced up-regulation of MUC1 was described elsewhere (39).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a stimulates the expression of MUC1 in A549 cells (39,40), human uterine epithelial cells (41), and human prostate cells (42). The molecular mechanism of the TNF-a-induced up-regulation of MUC1 was described elsewhere (39).…”
Section: Discussionmentioning
confidence: 99%
“…Second, TGN contains an ␣-tocopheroyl moiety, potentially giving it antioxidant activity (40). However, this alternative mechanism of action also appears unlikely based on a prior study demonstrating decreased MUC1 expression following treatment of epithelial cells with antioxidants (29). Finally, phosphorylation of ERK1/2 through the TNF-␣ receptor is known to activate MUC1 expression (25,29), and Bolden et al (8) recently demonstrated that treatment of human prostate cancer cells with TGN induced ERK1/2 phosphorylation via a PPAR␥-independent pathway.…”
Section: ϫ/ϫ (Iii Iv) Mice Following Inoculation With Pbs Vehicle Comentioning
confidence: 99%
“…However, this alternative mechanism of action also appears unlikely based on a prior study demonstrating decreased MUC1 expression following treatment of epithelial cells with antioxidants (29). Finally, phosphorylation of ERK1/2 through the TNF-␣ receptor is known to activate MUC1 expression (25,29), and Bolden et al (8) recently demonstrated that treatment of human prostate cancer cells with TGN induced ERK1/2 phosphorylation via a PPAR␥-independent pathway. However, this effect was only observed at relatively high TGN concentrations (40 M) and no effect on ERK1/2 activation was seen at the doses used in the present study (Ͻ 1.0 M).…”
Section: ϫ/ϫ (Iii Iv) Mice Following Inoculation With Pbs Vehicle Comentioning
confidence: 99%
“…Moreover, the airway epithelium also generates airway mucins that facilitate mucociliary clearance of inhaled particulates or microorganisms (103,104). Recent studies suggest that DUOX may participate in these responses as well, as illustrated by DUOX1-mediated production of epithelial mucins, such as MUC1 and MUC5AC, in response to inflammatory mediators such as neutrophil elastase or tumor necrosis factor (TNF)-α (105,106). Similarly, DUOX1 also mediates epithelial production of the neutrophil chemokine IL-8 in response to stimulation by bacterial lipopolysaccharide (LPS) (107).…”
Section: Functions Of Epithelial Duox: Host Defense and Intracellularmentioning
confidence: 99%